The initial stage of structural transformation of Aβ42 peptides from the human and mole rat in the presence of Fe2+ and Fe3+: Related to Alzheimer's disease. (December 2019) - Vahed, Mohammad; Sweeney, Aaron; Shirasawa, Hiroshi; Vahed, Majid
Graphical abstract: Highlights: Fe 2+ and Fe 3+ play distinct roles in folding and aggregation of Aβs. Fe 2+ was observed to be more likely than Fe 3+ to interact with imidazole rings of His. hAβ is more affected by Fe 2+ with three His residues than rAβ with two His residues. Fe 3+ can promote Aβs folding by forming stable β-sheet formations using an intramolecular tailoring approach. hAβ structures are unfavorable to form dimers whereas favors dimer formation in the C-terminal region. Abstract: The early stage of secondary structural conversion of amyloid beta (Aβ) to misfolded aggregations is a key feature of Alzheimer's disease (AD). Under normal physiological conditions, Aβ peptides can protect neurons from the toxicity of highly concentrated metals. However, they become toxic under certain conditions. Under conditions of excess iron, amyloid precursor proteins (APP) become overexpressed. This subsequently increases Aβ production. Experimental studies suggest that Aβ fibrillation (main-pathway) and amorphous (off-pathway) aggregate formations are two competitive pathways driven by factors such as metal binding, pH and temperature. In this study, we performed molecular dynamic (MD) simulations to examine the initial stage of conformational transformations of human Aβ (hAβ) and rat Aβ (rAβ) peptides in the presence of Fe 2+ and Fe 3+ ions. Our results demonstrated that Fe 2+ and Fe 3+ play key roles in Aβs folding and aggregation. Fe 3+ had a greater effect than Fe 2+ on Aβs' folding during intermolecular interactions and subsequently, had a greater effect in decreasing structural diversity. Fe 2+ was observed to be more likely than Fe 3+ to interact with nitrogen atoms from the residues of imidazole rings of His. rAβ peptides are more energetically favorable than hAβ for intermolecular interactions and amorphous aggregations. We concluded that most hAβ structures were energetically unfavorable. However, hAβs with intermolecular β-sheet formations in the C-terminal were energetically favorable. It is notable that Fe 2+ can change the surface charge of hAβ. Furthermore, Fe 3+ can promote C-terminal folding by binding to Glu22 and Ala42, and by forming stable β-sheet formations on the C-terminal. Fe 3+ can also pause the main-pathway by inducing random aggregations.